THE INFLUENCE OF GEN Z: PRODUCT INNOVATION ON MARKETING STRATEGIES IN THE BOTTLED MINERAL WATER (LE MINERAL) INDUSTRY - Dewi Puspaningtyas Faeni; Fatah Al Munawar (Cahaya Ilmu Bangsa, 2024)
This study investigates the influence of Generation Z and product innovation on the marketing strategy of the bottled mineral water industry in Indonesia. Generation Z, born between 1995 and 2010, influences marketing strategies with the characteristics of being creative, innovative, and caring for the environment. They encourage companies to develop innovative and environmentally friendly products to attract and retain consumer interest. An effective marketing strategy needs to adapt Generation Z's preferences for engaging and interactive visual content, as well as leverage social media as the primary platform for interaction with brands. This study uses a descriptive-analytical approach by collecting data from literature and case studies of the bottled mineral water industry in Indonesia. The findings show that the integration of a deep understanding of Generation Z behavior and the ability to innovate in products is key to the success of marketing strategies. This research contributes to the marketing literature by providing insights into how companies can improve their marketing strategies, focusing on the characteristics and preferences of Generation Z as well as the importance of product innovation in the face of fierce market competition.